Development of quizizz based interactive learning media using a contextual approach for ratio lesson - Ummatul Arifah; Rahma Ramadhani (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Mathematics instruction requires innovative teaching materials to help students grasp concepts more easily and improve learning outcomes. However, the use of technology-based interactive learning media for ratio material at the junior high school/MTs level, particularly at MTsN 15 Jombang, is still not optimal, as evidenced by the results of observations and interviews conducted with seventh-grade mathematics teachers. Consequently, the learning process tends to be unengaging, student participation remains low, and learning outcomes are unsatisfactory. This issue is particularly urgent because ratio is a fundamental mathematical concept that serves as a prerequisite for learning more advanced topics, making students' conceptual understanding at this stage essential for their future mathematical achievement. Therefore, there is a need to develop engaging technology-based learning media that can enhance students' motivation, conceptual understanding, and learning outcomes. Therefore, this study aims to develop an interactive learning medium based on Quizizz for seventh-grade ratio material that meets the criteria of being valid, practical, and effective in improving student learning outcomes. This study employed the ADDIE research and development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The study was conducted at MTsN 15 Jombang with seventh-grade Class B students as the participants. Product testing was carried out in two phases: a small-group trial involving 6 students and a large-group trial involving 29 students. Research data were collected through observations, questionnaires, and tests using media expert validation sheets, content expert validation sheets, student response questionnaires, and pretest–posttest instruments. Data were analyzed using validity and practicality percentages, as well as the N-Gain test to determine the effectiveness of the media. The results showed that the media obtained validity scores of 92.5% from media experts and 87.5% from content experts, both categorized as highly valid. Student responses reached 83.5%, indicating that the media was highly practical. Furthermore, the N-Gain score of 0.71 was classified as high, demonstrating that the developed media effectively improved students' learning outcomes. Thus, the Quizizz-based interactive learning media is valid, practical, and effective and can serve as an alternative learning medium for teaching ratio in junior high school mathematics.